A web of relations: co-production arrangements in urban sanitation infrastructure provision in informal settlements in Arusha City, Tanzania - Abwe, Furaha (School of Architecture, Planning and Geomatics, 2020)
Many city governments and actors have tested approaches or models and technological developments to address urban service crises. But this has tended to be without much success, as the service delivery gap keeps widening, leading to governance failure. One response to this decline in governance capacity has been the evolution of co-production arrangements. The overarching aim of this thesis was to examine the co-production arrangements of urban sanitation infrastructure provision among multiple actors in informal settlements, and to interrogate whether the predominance of such arrangements was indicative of an alternative form of city governance. Two wards within Arusha city (Tanzania) were selected as case studies. A range of research methods was employed to uncover the landscape of actors involved, and to explore co-productive processes, socio-cultural aspects and other complexities shaping sanitation provision in the two selected informal settlements. Case study methodology was used with a range of data collection methods (household surveys, focus group discussions, document review and semi-structured interviews). The study adopted a relational approach informed by ActorNetwork Theory as the analytical framework for understanding the human-material interactions in the sanitation chain. Key findings indicate that co-production serves a public function, but it is not recognised as such in Tanzanian public policy. Individual and collective co-production arrangements have been established that bring together various state and non-state actors in the sanitation chain to form networks. These networks make service delivery possible, which one actor alone could not deliver. The study reveals that sanitation infrastructure in informal settlements is largely provided by the household, although some are either inactive or captured co-procuders. Further, the narratives indicate that complexities and the contextual factors (including gender-based power dynamics, social norms, values, traditions and culture) shape access to sanitation facilities in the city of Arusha. The study found that the exclusion of women and children from sharing toilet facilities motivated Maasai men to practice defection in open areas. Further, this study speculates on an alternative form of governing city affairs based on actor-networks in the co-production process: co-productive networked governance. Future research is needed to examine how co-productive networked governance could be integrated into the existing city governance structures and how informal governance arrangement could be recognised and enhanced.